Pengembangan Buku Cerita Ekologi Hutan Mangrove untuk Menunjang Karakter Cinta Lingkungan pada Siswa Sekolah Dasar: (Development of a Mangrove Forest Ecology Storybook to Support Environmental Love Characters in Elementary School Students) - Istiqomah, Risci Afif; Magdalena, Ellen Sukma Mega; Sari, Tri Astuti Nina; Aulia, Tiara Dwi; yanto, Yudi; Wakhidah, Anisatu Z. (BIODIK, 2024)
The development of the mangrove forest ecology story book was motivated by the critical nature of the mangrove forest ecosystem in Indonesia. Mangrove forests have great benefits both ecologically and economically. If the population of mangrove forests becomes smaller and smaller, it will have negative impacts on living creatures and the environment. Storybooks are the right media to increase children's understanding of the importance of protecting mangrove forests. Therefore, this research aims to develop learning media in the form of story books to foster the character of loving the environment in elementary school students about the importance of preserving and protecting mangrove forests. This research is development research (R&D) with a 4D model (define, design, development, and disseminate). Based on the results of interviews with teachers at SD Negeri 3 Teluk Pandan, information was obtained that the school had never used storybooks in the learning process. From this problem, a story book was then developed to provide a broader understanding of natural science for elementary school students. The storybook development was made using the Procreate application version 5.3.7. The mangrove ecology story book succeeded in getting "very decent" validation from material expert validators with a percentage of 87.5% and from media expert validators with a percentage of 93.75%. The test results of this product also showed a "very good" qualification according to teacher responses of 92.5% and student responses of 93.3%. These findings lead to the conclusion that the created storybook satisfies the requirements to be a useful substitute teaching tool in primary schools.The contribution to the development of this storybook can be used as a fun learning medium, providing elementary school students with an understanding of the management and preservation of mangrove forests. Abstrak. Pengembangan buku cerita ekologi hutan mangrove dilatar belakangi oleh kritisnya ekosistem hutan mangrove di Indonesia. Hutan mangrove mempunyai manfaat besar baik secara ekologi maupun ekonomi, bila hutan mangrove semakin lama semakin sedikit jumlah populasinya, maka akan mengakibatkan dampak negatif bagi makhluk hidup dan lingkungan. Buku cerita merupakan media yang tepat untuk meningkatkan pemahaman anak tentang pentingnya menjaga hutan mangrove. Oleh karena itu, tujuan dari penelitian ini adalah untuk menciptakan sumber belajar dalam bentuk buku bergambar yang akan mengajarkan anak-anak sekolah dasar tentang nilai-nilai melestarikan dan menjaga hutan mangrove serta membantu mereka memperoleh apresiasi terhadap lingkungan. Penelitian ini merupakan penelitian pengembangan (R&D) dengan menggunakan model 4D (define, design, development, dan desiminate),. Selama wawancara dengan guru di SD Negeri 3 Teluk Pandan, diketahui bahwa buku cerita belum pernah digunakan di kelas. Dari permasalahan ini, kemudian di kembangkan buku cerita untuk memberikan pemahaman lebih luas mengenai ilmu pengetahuan alam untuk siswa sekolah dasar. Pengembangan buku cerita dibuat dengan menggunakan aplikasi procreate versi 5.3.7. Buku cerita ekologi mangrove berhasil mendapatkan validasi "sangat layak" dari validator ahli materi dengan presentase 87,5% dan dari validator ahli media dengan presentase 93,75%. Hasil uji coba produk ini juga menunjukkan kualifikasi "sangat baik" menurut respon guru sebesar 92,5% dan respon siswa sebesar 93,3%. Kesimpulan dari hasil tersebut adalah bahwa buku cerita yang telah dikembangkan memenuhi standar untuk menjadi media pembelajaran alternatif yang efektif di sekolah dasar. Kontribusi pengembangan buku cerita ini dapat digunakan sebagai media pembelajaran yang menyenangkan, memberikan pemahaman kepada siswa sekolah dasar dalam pengelolaan dan pelestarian hutan mangrove.